Estimating the impact of the Balassa-Samuelson effect in transition economies - Adriana Lojschová (Institute for Advanced Studies (IHS), 2003)
The Balassa-Samuelson (BS) effect is usually considered as the prime explanation of the continuous real exchange rate appreciation of the central and east European (CEE) transition countries against their western European counterparts. This paper tries to explain relative price differentials observed over the past decade between four CEE economies - Slovakia, the Czech Republic, Hungary and Poland - and Euro area in terms of productivity growth differentials. Using panel estimation techniques, we find strong empirical evidence in favour of the BS hypothesis. Furthermore, relaxing some of the assumptions (i.e. PPP holds for tradable goods) results in little support of BS hypothesis. Our estimates of the BS term suggest that the Balassa-Samuelson effect in these 4 CEE countries does not have to be as sizeable as other studies propose.
Keywords: E31; F31; C23; 330; Balassa-Samuelson effect; Purchasing Power Parity (PPP); real exchange rate appreciation; transition economies